Construction and application of grid management in nursing information construction (网格化管理在护理信息建设中的构建与应用) - WANG Tingting (王婷婷); GUO Xiujun (郭秀君); LIANG Junni (梁俊妮); HONG Yanyan (洪艳燕); QIAN Weiqing (钱卫庆) (中西医结合护理)
Objective To explore the role of grid management mode in nursing information management, and to provide reference for nursing information management mechanism. Methods The nursing units were divided into large, medium and small grids, and the viewpoints and methods based on the grid management theory were established to form a plane and deep network management method with clear division of labor and appropriate coordination. To compare the application efficacy of grid management between two different period: May 2018 to May 2019 as before-intervention period, May 2019 to May 2020 as after-intervention period. The primary outcomes were implementation condition of medical orders, nursing inspection conditions, Jingyi-512 training efficacy and patient satisfaction. Results The rates of standardized implementation of medical orders, nursing inspection, Jingyi-512 training and patient satisfaction was greatly improved after intervention compared with those before intervention (P＜0. 05). The qualified rate of double-check on blood transfusion indexes reached100. 00%. Conclusion The grid management of nursing cells is an effective and effective management mode, which can quickly form a good situation of "hospital has a network, a network has a grid, a grid has a person, and a person takes his responsibility", which makes the management more scientific and achieves the goal of fine management. (目的 探讨网格化管理模式在护理信息管理中的作用, 为护理信息管理机制提供参考依据。方法 选取南京市中医院护理单元48个, 将2018年5月—2019年5月实施网格化管理前设为实施前, 2019年5月开始实施网格化管理, 将2019年5月—2020年5月设为实施后。比较实施护理网格化管理前后医嘱执行规范性、巡视情况、“京颐512”培训考核、患者满意度。记录实施护理网格化管理后相关功能的改善情况。结果 实施护理信息网格化管理后, 医嘱执行规范性、巡视情况、“京颐512”培训考核、患者满意度均优于实施前, 差异有统计学意义(P＜0. 05)。实施护理信息网格化管理后, 输血质量监测指标双人核查符合率为100. 00％。结论 网格化管理各护理单元格, 是一种立竿见影、行之有效的管理模式, 能快速形成“医院有网、网内有格、格内定人、人担其责”的良好局面, 使管理更加科学, 达到了精细化管理的目的。)